2018
DOI: 10.20965/jdr.2018.p1049
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Life Expectancy and Disaster Risk

Abstract: A healthy community is a community resilient to disaster. The Sendai Framework for Disaster Risk Reduction considers disaster impacts on health and encourages the implementation of disaster medicine and access to mental health services. Life expectancy (LE) is a basic statistic that indicates public health achievements and social development, including the health system, infrastructure, and accurate vital statistics. Thus, we hypothesized that LE corelates with disaster risk and strategies to achieve long LE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Source: authors. Variable Reference literature Key finding(s) Exposure International air connectivity ( Findlater & Bogoch, 2018 ); ( Keita, 2020 ) Air travel is leading to an increase in the frequency of reach of infectious diseases, more connected countries have higher exposure Participation in international trade ( Ibarrarán, Ruth, Ahmad, & London, 2009 ); ( Wiedmann & Lenzen, 2018 ) Increased dependency on global network can have ripple effect in different countries, developing countries appear to be disproportionately affected Air pollution ( Fattorini & Regoli, 2020 ); ( Frontera, Cianfanelli, Vlachos, Landoni, & Cremona, 2020 ) Chronic atmospheric pollution is likely to favor the spread of COVID-19 Comorbidity ( Wang, Li, Lu, & Huang, 2020 ); ( Sanyaolu et al, 2020 ) People with comorbidity are more like to be severely affected by COVID-19 Susceptibility Population Density ( Ahmadi, Sharifi, Dorosti, Ghoushchi, & Ghanbari, 2020 ); ( Bhadra, Mukherjee, & Sarkar, 2021 ); ( Liu, Liu, & Guan, 2021 ) The spread of COVID-19 is positively correlated to population density Poverty ( Mamun & Ullah, 2020 ); ( Alkire, Dirksen, Nogales, & Oldiges, 2020 ) Poor people are more susceptible to the socio-economic impacts of COVID-19 Health ( Egawa et al, 2018 ); ( Frank & Wali, 2021 ) Healthier communities are more resilient to disaster risk, life expectancy is an important indicator of disaster risk Informality ( Wilkinson, 2020 ); ( ...…”
Section: Methodsmentioning
confidence: 99%
“…Source: authors. Variable Reference literature Key finding(s) Exposure International air connectivity ( Findlater & Bogoch, 2018 ); ( Keita, 2020 ) Air travel is leading to an increase in the frequency of reach of infectious diseases, more connected countries have higher exposure Participation in international trade ( Ibarrarán, Ruth, Ahmad, & London, 2009 ); ( Wiedmann & Lenzen, 2018 ) Increased dependency on global network can have ripple effect in different countries, developing countries appear to be disproportionately affected Air pollution ( Fattorini & Regoli, 2020 ); ( Frontera, Cianfanelli, Vlachos, Landoni, & Cremona, 2020 ) Chronic atmospheric pollution is likely to favor the spread of COVID-19 Comorbidity ( Wang, Li, Lu, & Huang, 2020 ); ( Sanyaolu et al, 2020 ) People with comorbidity are more like to be severely affected by COVID-19 Susceptibility Population Density ( Ahmadi, Sharifi, Dorosti, Ghoushchi, & Ghanbari, 2020 ); ( Bhadra, Mukherjee, & Sarkar, 2021 ); ( Liu, Liu, & Guan, 2021 ) The spread of COVID-19 is positively correlated to population density Poverty ( Mamun & Ullah, 2020 ); ( Alkire, Dirksen, Nogales, & Oldiges, 2020 ) Poor people are more susceptible to the socio-economic impacts of COVID-19 Health ( Egawa et al, 2018 ); ( Frank & Wali, 2021 ) Healthier communities are more resilient to disaster risk, life expectancy is an important indicator of disaster risk Informality ( Wilkinson, 2020 ); ( ...…”
Section: Methodsmentioning
confidence: 99%
“…Goudet et al (2011) confirmed that barriers to appropriate IYCF practices exist in normal times and that they were escalated in the flood, thereby leading to extremely poor nutritional health in Dhaka slums in Bangladesh. Egawa et al (2018) clarified that malnutrition in children under five worsened the INFORM disaster risk index (European Commission 2021), associated with low life expectancy. According to The Sphere Project ( 2011), the time necessary to reach the minimum standard depends on resources, access, insecurity, and living standards of an area before a disaster.…”
Section: Pre-disaster Malnutritionmentioning
confidence: 99%
“…Understanding their specific cultural, social, psychological, economic, and physical needs are all crucially important forces for building capacity for disaster preparedness in terms of nutrition. Disaster risk is the potential loss of life, injury, or destroyed or damaged assets which can occur to a system, society, or a community during a specific period of time, determined probabilistically as a function of hazard, exposure, vulnerability, and capacity (UNDRR 2017; Egawa et al 2018Egawa et al , 2020. Resilience can be improved when private individuals and institutions prepare by acting to build a culture of prevention and safety in a broad sense (UNDRR 2019).…”
Section: Disaster Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…The word count of "health" in Sendai Framework has increased to 34 words from the zero in the preceding 1 st framework, Yokohama Strategy (IDNDR, International Decade for Natural Disaster Reduction 1995), and the 2 nd framework, Hyogo Framework for Action (HFA) (ISDR, International Strategy for Disaster Reduction 2005). Interestingly, the disaster risk index has a strong correlation with the life expectancy of the country, suggesting that health improvement is necessary in disaster risk reduction (Egawa et al 2018).…”
Section: Disaster Terminology and Global Identifier (Glide) Numbermentioning
confidence: 99%